The extent of women's empowerment across rural-urban areas and wealth categories and its role in nutrition outcomes of family members in Uttar Pradesh, India - Palani Samy, Venkatesh; Vellaichamy, Sangeetha; Girish Kumar, Jha; Sharma, Nitin; Babu, Suresh Chandra (Agricultural and Applied Economics Association, 2023)
In the Indian family setting, women play a crucial role in the overall development of the households. Hence, development agencies and government programs mainly target women, assuming that empowering women would improve families. Given this background, we aim to construct a women's empowerment index (WEI) that encompasses all these domains and captures nutrition improvement for their and their family members. We assigned the weights based on principal component analysis (PCA). Then, we examine the extent of empowerment and nutrition outcomes of the family members across the wealth category and place of residence (rural-urban setting). Finally, we validate the WEI by analyzing the relationship between WEI and nutrition outcomes of family members through logit analysis. We used Uttar Pradesh data from National Family Health Survey (NFHS) -5 conducted in 2019-21 for the study. We found a positive relationship between household wealth and women's empowerment, indicating the vulnerability of women in poor families, especially in rural areas. Our results also suggested that women's empowerment differs across educational backgrounds and places of residence. Finally, we found that the prevalence of malnutrition is negatively associated with women's empowerment, especially children and women. These findings highlight the need for promoting women's empowerment-based policies and interventions to address the malnutrition problem